2012
DOI: 10.1111/j.1743-6109.2012.02739.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α, Erectile Dysfunction, and NADPH Oxidase-Mediated ROS Generation in Corpus Cavernosum in High-Fat Diet/Streptozotocin-Induced Diabetic Rats

Abstract: Introduction Patients with diabetes-associated erectile dysfunction (ED) are characterized by an increase in circulating tumor necrosis factor-alpha (TNF-α). However, no study has indicated whether and how TNF-α plays a role in the pathogenesis of ED associated with diabetes. Aim We examined the effects and potential mechanism of infliximab (INF), a chimeric monoclonal antibody to TNF-α, on reactive oxygen species (ROS) gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 53 publications
(83 reference statements)
0
34
0
Order By: Relevance
“…TNFR1 has a ubiquitous distribution (endothelial and smooth muscle cells), whereas TNFR2 expression is mostly confined to cell of hematopoietic origin (Ryffel and Mihatsch, 1993). TNFR1 selectively mediates the majority of the toxic and pro-atherogenic effects of TNFa (Zhang et al, 2010) and is also expressed by the penis (present study and Carneiro et al, 2010;Long et al, 2012). However, the relative abundance of TNFa and TNFR1 mRNA in rabbit penis was rather low and similar to other urogenital tissues.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…TNFR1 has a ubiquitous distribution (endothelial and smooth muscle cells), whereas TNFR2 expression is mostly confined to cell of hematopoietic origin (Ryffel and Mihatsch, 1993). TNFR1 selectively mediates the majority of the toxic and pro-atherogenic effects of TNFa (Zhang et al, 2010) and is also expressed by the penis (present study and Carneiro et al, 2010;Long et al, 2012). However, the relative abundance of TNFa and TNFR1 mRNA in rabbit penis was rather low and similar to other urogenital tissues.…”
Section: Discussionmentioning
confidence: 38%
“…Infliximab did not normalize T level, but significantly increased eNOS expression and normalized Ach responsiveness in penis. Similar effects of infliximab on penile function have already been observed in a rat model of HFD/STZ type 2 diabetes (Long et al, 2012). Conversely, infliximab treatment did not affect either the relaxant response to SNP (a NO donor, which bypasses endogenous NO formation), or the expression of genes downstream NO signaling (GCa3, CGb3, PKG1).…”
Section: Discussionmentioning
confidence: 48%
“…Thus, the The high blood glucose in diabetes mellitus puts the body in a state of high oxidative stress, with damage to the corpora cavernosa nerves and endothelial cells, as well as inactivation of neuronal and endothelial nitric oxide synthase, leading to decreased production of nitric oxide and diabetes mellitus erectile dysfunction [18,19] . In the rat model of diabetic ED caused by streptozotocin, the products of oxidative stress, such as malonaldehyde, were accumulated, while antioxidant substances (eg, SOD and glutathione) were decreased, resulting in increased ROS levels in the corpus cavernosum [32,33] . Recent investigations have demonstrated that ROS affect the self-renewal and differentiation of bone marrow mesenchymal stem cells, accelerate aging in stem cells and endothelial progenitor cells, increase apoptosis and reduce the self-healing of damaged blood vessels [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that hyperglycemia in diabetics leads to smooth muscle dysfunction by the oxidation of low density lipoprotein and increased production of free-oxygen radical species, in addition to mitochondrial fragmentation and cellular apoptosis which leads to endothelial dysfunction resulting in decreased the amount of Nitrous Oxide (NO) production in cavernous tissue [15,16].…”
Section: Introductionmentioning
confidence: 99%